THE ROLE OF COURSES IN INFLUENCING SMART CONSUMER BEHAVIOUR OF SENIOR HIGH SCHOOL STUDENTS IN RURAL AND URBAN AREAS - Tio Putra Mahardika; Lilik Noor Yuliati (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2022)
Consumer education interventions through formal education can increase knowledge, attitudes, and behaviour to become smart consumers who can enforce their rights, carry out their obligations, and protect themselves from harmful goods or services. This study aims to analyze differences in awareness of consumer education materials, sources of information, attitudes, and behaviour as savvy consumers in high school students in rural and urban Bogor and the factors that influence smart consumer behaviour. This study used a cross-sectional study design and involved two senior high schools located in the rural and urban areas of Bogor. The location selection was performed purposively, considering that the school implemented the Education Unit Level Curriculum (KTSP) and used the Electronic School Book (BSE). The sampling technique used random cluster sampling with a sample size of 129 high school students, 68 students in rural areas and 61 students in urban areas. The results showed significant differences in the material awareness of consumer rights variables and the three attitude dimensions. On the contrary, there was no difference in material awareness of consumer obligations, objective knowledge of rights and obligations and significant smart consumer behaviour on smart consumer behaviour in both regions. Students' age, objective knowledge about consumer obligations, and attitudes (affective and conative dimensions) significantly positively affect smart consumer behaviour in high school students.